Promoting Tax Compliance in Kosovo with Behavioral Insights - Hernandez, Marco; Karver, Jonathan; Negre, Mario; Perng, Julie (World Bank, Washington, DC, 2019)
As in many countries, tax collection is a development challenge in Kosovo. Kosovo is one of the poorest and youngest countries in Europe in terms of gross domestic product (GDP) per capita and both demographics and statehood. The lack of an independent monetary policy — given that Kosovo has adopted the euro as the national currency — means that ensuring the sustainability of fiscal policy is critical. However, limited tax revenues hamper the government's ability to address economic cycles. Between 2011 and 2017, total government revenue amounted to about 14 percent of GDP, below the average of 19 percent among countries in Europe and Central Asia. Unlike other countries, Kosovar government relies on taxes for more than 85 percent of its revenues. Mobilizing tax revenues is therefore critical. The Tax Administration of Kosovo (TAK) requested assistance from the World Bank and the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) to address this challenge using an evidence-based approach. To this end, the World Bank and GIZ applied behavioral insights to promote tax compliance among specific groups of taxpayers. Three experiments were designed, implemented, and evaluated in 2018 that involved sending behaviorally informed reminders using letters, e-mails, and short messaging service (SMS) messages to various groups of taxpayers to induce timely and honest declarations and payments. The short-term objective of these trials was to increase the number and timeliness of tax declarations. Simple, behaviorally designed messages were effective in inducing tax declaration. Messages helped raise the tax declaration rate by an average of around 3 percentage points during a period of between four and six weeks. Among personal income tax (PIT) declarations, this represents a 59 percent increase in compliance, equivalent to over 200 more annual tax declarations among participants. The likelihood of payment rose in many instances, and no significant difference was found in the amounts of taxes paid. Lessons from the tax experiments in Kosovo highlight the benefits of rigorous impact evaluation and the need to establish processes that help integrate tax collection functions and data systems.